Analysis of Modification of Car AC Compressor to Split AC Compressor on Cooling Rate - Mokh Hairul Bahri; Adi Pratama Putra (Unit Publikasi Ilmiah, P3M, Politeknik Negeri Bali, 2022)
Refrigeration or cooling technology is increasing, especially regarding the coolant, almost all new vehicles now use air conditioning to condition the air in the vehicle cabin, but there are still many aspects that currently have not been paid much attention, especially to compressors, compressors for now still rely on the engine as a direct driver which makes fuel consumption more wasteful and reduces the performance of the vehicle. The purpose of this research is to modify a conventional compressor into an electric compressor by utilizing a split ac compressor. The research method uses the direct experimental method, can a split ac compressor replace a conventional compressor. Testing without changing a lot of the cooling system on the car, only changing the compressor without any other changes. The results of the research on split ac compressors can be applied to cars, but the cooling rate is slower than car ac compressors.